Kinetic Monte Carlo simulation for homogeneous nucleation of metal nanoparticles during vapor phase synthesis. Issue 1 (12th August 2017) - Davari, Seyyed Ali; Mukherjee, Dibyendu
Abstract : We present a free‐energy driven kinetic Monte Carlo model to simulate homogeneous nucleation of metal nanoparticles (NPs) from vapor phase. The model accounts for monomer‐cluster condensations, cluster–cluster collisions, and cluster evaporations simultaneously. Specifically, we investigate the homogeneous nucleation of Al NPs starting with different initial background temperatures. Our results indicate good agreement with earlier phenomenological studies using the Gibbs# free energy formulation from Classical Nucleation Theory (CNT). Furthermore, nucleation rates for various clusters are calculated through direct cluster observations. The steady‐state nucleation rate estimated using two different approaches namely, the Yasuoka‐Matsumoto (YM) and mean first passage time (MFPT) methods indicate excellent agreement with each other. Finally, our simulation results depict the expected increase in the entropy of mixing as clusters approach the nucleation barrier, followed by its subsequent drastic loss after the critical cluster formation resulting from first‐order phase transitions. © 2017 American Institute of Chemical Engineers AIChE J, 63: 18–28, 2018